Excellent educare tuition centre / Marsytah Shaari... [et al.] - Shaari, Marsytah; Boyou, Natasha Melissa; A Mansur, Saniayah; Zaini, Zarina (Faculty of Administrative Science & Policy Studies, 2005)
Committing to the business domain expressly in education directly will help the Ministry Of Education to increase the education level or standard in Malaysia. Barrel to the government’s aspiration is to produce the educated and excellent younger for the new millennium era. That is why we come out with this business in order to overcome the barrel. Apart from that, in order to realize the government's encouragement, to increase the number of excellent students in our country, to increase the quality of education and to produce more expertise and professional in fieldwork, therefore we come out with this business. Based on the objectives of Excellent Educare Tuition Centre, we will provide a space for the USPR, PMR, SPM & STPM candidates and also for those are the former students (repeaters ), to improve their quality of studies. Besides that, we come out with the latest technology approach, meaning that our services are totally technology-oriented. The teachers will conduct the learning session using the projector and laptop. This will be the best way to attract student's attention and will avoid the feeling of the bore during the learning session. These actually comply with our target to establish the best learning condition for the student.